EXPLORING THE EFFECTS OF GAMIFICATION IN GRAMMAR INSTRUCTION ON BEGINNER EFL STUDENTS’ GRAMMATICAL UNDERSTANDING AND LEARNING MOTIVATION - Citra Dwi Safitri; A. Kamariah; Muhammad Fahri Jaya Sudding; Musdalifah (Program Studi Pendidikan Bahasa Inggris, 2026)
Gamification has gained increasing attention in EFL learning because it can create more engaging and interactive classroom environments. However, beginner EFL students often experience difficulties in understanding grammar and maintaining learning motivation through traditional instructional methods. This study aimed to explore the effects of gamification on beginner EFL students’ grammatical understanding and learning motivation through the use of Quizizz and Wordwall in grammar instruction. This study employed a descriptive qualitative research design involving 20 first-year university students enrolled in a Basic English Grammar course. Data were collected through close-ended questionnaires and semi-structured interviews with eight selected participants. The findings revealed that gamification positively supported students’ grammatical understanding through interactive practice, repeated exposure, and immediate feedback. In addition, gamified activities increased students’ motivation, engagement, confidence, and participation during grammar lessons. Students perceived grammar learning as more enjoyable and less monotonous when using gamified platforms. The study suggests that gamification can serve as an effective instructional approach to support grammatical understanding and learning motivation among beginner EFL students.